2003
DOI: 10.1080/00150190390205997
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and Neutron Studies of Antiferroelectric Phase Transition in Cu(HCOO) 2 ·4H 2 O

Abstract: X-ray diffraction and incoherent inelastic neutron scattering studies are performed to clarify the phase transition mechanism of Cu(HCOO) 2 ·4H 2 O. Contrary to the previous electrical study, we find no evidence of the existence of an intermediate ferrielectric phase. We determine the accurate antiferroelectric structure. It turns out that the atomic arrangement of the Cu(HCOO) 2 layers remains unchanged through the phase transition, while the antiferroelectric H 2 O layers take one of two disordered paraelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…We found that some peaks lying in the range of 1 ¼ 65 -90 meV become broad above T t ¼ 235:5 K: The modes in this energy range can be assigned empirically to the out-ofplane H 2 O librational modes. Considering the structure of the H 2 O layer [2], we conclude that the disorder of the H 2 O layer in the PE phase is induced by the rotation of the H 2 O molecules with the out-of-plane hydrogen motion.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We found that some peaks lying in the range of 1 ¼ 65 -90 meV become broad above T t ¼ 235:5 K: The modes in this energy range can be assigned empirically to the out-ofplane H 2 O librational modes. Considering the structure of the H 2 O layer [2], we conclude that the disorder of the H 2 O layer in the PE phase is induced by the rotation of the H 2 O molecules with the out-of-plane hydrogen motion.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 1 shows the AFE structure which is formed by two kinds of layers; an H 2 O layer and a Cu(HCOO) 2 layer. The crystal structure analysis has revealed that the H 2 O layer is disordered above T t and ordered below T t , while the Cu(HCOO) 2 layer remains practically unchanged through T t [2]. This indicates that the phase transition of CFT can be regarded as that of "quasi-two-dimensional ice".…”
Section: Introductionmentioning
confidence: 88%
“…The single crystals of CFT were grown by slow cooling an aqueous solution from about 40 1C at a rate of 1 1C/day [4]. The DC susceptibility and magnetization measurements of the single crystal and powder samples were calculated using a superconducting quantum interference device (SQUID) magnetometer (Quantum Design MPMS-5S).…”
Section: Methodsmentioning
confidence: 99%
“…Formate, the smallest carboxylic ligand, was studied several decades ago because of the unusual physical properties observed in hydrated transition metal formate compounds. , A renewed interest in formate based frameworks has occurred recently . The formate ligand adopts different bridging modes depending on the coordination environment .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the neighboring metal centers are effectively coupled via the formate bridging ligand leading to interesting magnetic behavior. The structure–property relationship of hydrated transition metal formates M (HCOO) 2 · x H 2 O ( M = transition metals) and their deuterated forms, ,, anhydrous metal formates [ M (HCOO) 2 ], metal formates with monodentate ligands [ M (HCOO) 2 ·2L] (L = urea), metal formates with bidentate ligands [ M (HCOO) 2 L] (L = 4,4′-bipyridine, pyrazine), and metal formates with solvents [ M (HCOO) 2 · n (solvent)] have been studied. In many of these compounds the behavior of the magnetic susceptibility below the Néel temperatures suggested weak ferrimagnetism.…”
Section: Introductionmentioning
confidence: 99%